RELIABILITY SENSITIVITY ANALYSIS OF THE DRIVE SHAFT AND OPTIMIZE BASED ON FOUTTH-MOMENT TECHNIQUE - LIU Zhe; TAO FengHe; JIA ChangZhi (Jixie qiangdu)
Numerical method for reliability sensitivity design is presented based on fourth moment technique,track-laying vehicle drive shaft mechanical model is set to discuss and analyze only know the mechanical components under random distribution parameters before four moments of the mechanical components of the sensitivity of the analysis and design problems,reliable transmission shaft the degree of sensitivity variation with its various structural parameters when changes are given,the effects of changes in the structural parameters of the drive shaft of the reliability and provide a theoretical basis for the reliability optimization of the drive shaft,and then based on the results of the sensitivity analysis of structural improvements to the drive shaft research,the production can be very useful if it extended to correlated area of machine sensitivity design.